THE IMPACT OF NATIONAL CULTURE ON BILATERAL TRADE IN VIETNAM - Tu, Dr. Phan Anh; Song, Prof. Dr. Nguyen Van; Thuan, Dr. Tran Duc; Hien, Dr. Nguyen Thi Minh; Ha, Dr. Thai Van; Phuong, Dr. Pham Thi Lan; Uan, Dr. Tran Ba; Hung, Nguyen Nang (The journal of contemporary issues in business and government, 2021)
The purpose of this paper is to examine whether or to what extent national culture influences bilateral trade flows between Vietnam and its trading partners. Using a panel dataset of 52 countries from 2001 till 2011 and six cultural dimensions of Hofstede, the regression analysis performed by gravity model shows that national culture and bilateral trade flows between Vietnam and trading partners are significantly correlated. This study's implications may help macro-policy makers devise better export promotion policies and boost the volume of bilateral trade between Vietnam and other countries around the world.